'Bigger' after all? The Effect of Structural Policy Coordination Authorities on the Multidimensionality of Policy Output. (5th April 2022) - Ophey, Kristina; Schwalbach, Jan
Abstract: To be 'bigger on big things', Jean‐Claude Juncker reformed the European Commission's organizational set‐up by adding another hierarchical layer to its political sphere. Vice‐Presidents shall foster coordination between departmental Commissioners when drafting policies so that these are more multidimensional in kind. Taking an actor‐centred organization theoretical perspective, complemented by principal–agent reasoning, we conceptualize these as structural policy coordination authorities . We hypothesize that this organizational manipulation to a core executive's typical multidivisional set‐up incentivizes silo‐focused actors to coordinate more across policy sectors. Hence, the coordination dilemma that typically confronts core executives might be counteracted, resulting in more multidimensional policy output. Constituting a 'case in time', we assess whether Commission policy output has changed systematically after the Juncker reform. Using newly developed indicators for policy multidimensionality, we evaluate all legislative proposals developed under the Juncker and Barroso II Commissions. We find that proposals under Juncker are indeed 'bigger' than before.